A New Approach for the Electron Beam Diagnostic Using Diffraction Radiation Disphase Target - Shkitov D. A. Dmitriy Andreevich; Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Urakawa J. Junji (2016, 2016)
Title screen